2016
DOI: 10.1111/jcms.12442
|View full text |Cite
|
Sign up to set email alerts
|

What Type of Power has the EU Exercised in the Ukraine–Russia Crisis? A Framework of Analysis

Abstract: What impact has the Russia–Ukraine crisis had on the EU as a foreign policy actor? Most studies examine how the EU has evolved as an actor over time of its own initiative, but tend to discount the role that the external context or structure of the international system might play in constraining or enabling the EU's exercise of power. This Special Issue seeks to understand the EU's influence in the world through recognizing its embeddedness in an unpredictable and uncertain international system. Specifically, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…A weakened transatlantic relationship could also go hand in hand with a more cohesive and stronger Union, if the member states unify in their responses to the crises they are facing, suggesting the emergence of what we call an autonomous EU superpower. Studies have for example suggested that crises can trigger more EU integration to address shared challenges, leading to new policies or more delegation of powers to EU institutions in a variety of different policy fields affected by crisis (Cross and Karolewski 2017;Mény 2014;Majone 2005;Genschel and Jachtenfuchs 2014;Schmitter 1970). In fact, the EU has already responded to developments such as the Ukraine crisis by further strengthening EU foreign and security cooperation (Cross and Karolewski 2017;Howorth 2018, 523-537;Riddervold 2018;Smith 2018b, 605-620), by claiming to take the global lead in the fight against climate change (Cross 2018, 571-586), by remaining committed to uphold the Iran Nuclear Accord, and it is strengthening its ties with China in support of the global, liberal economic order.…”
Section: Framework: Crises and Eu-us Relationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A weakened transatlantic relationship could also go hand in hand with a more cohesive and stronger Union, if the member states unify in their responses to the crises they are facing, suggesting the emergence of what we call an autonomous EU superpower. Studies have for example suggested that crises can trigger more EU integration to address shared challenges, leading to new policies or more delegation of powers to EU institutions in a variety of different policy fields affected by crisis (Cross and Karolewski 2017;Mény 2014;Majone 2005;Genschel and Jachtenfuchs 2014;Schmitter 1970). In fact, the EU has already responded to developments such as the Ukraine crisis by further strengthening EU foreign and security cooperation (Cross and Karolewski 2017;Howorth 2018, 523-537;Riddervold 2018;Smith 2018b, 605-620), by claiming to take the global lead in the fight against climate change (Cross 2018, 571-586), by remaining committed to uphold the Iran Nuclear Accord, and it is strengthening its ties with China in support of the global, liberal economic order.…”
Section: Framework: Crises and Eu-us Relationsmentioning
confidence: 99%
“…After all, the transatlantic relationship has been one of the key features of international relations since the end of World War II . Much has also been written about the impact of different crises on EU policies and institutions (examples include special issues by; Cross and Karolewski 2017;Copelovitch, Frieden and Walter 2016;Falkner 2016;Graziano and Halpern 2016;Hooghe, Laffan and Marks 2018;Laffan 2016;Niemann and Zaun 2018). Surprisingly little has however been written about how, if in any way, this context of crises relate to and impact EU-US relations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crisis provides a chance for the EU to revisit how it can and will exercise power. It is also a critical test for the EU's foreign policy post-Lisbon -it has a chance to enable the EU's exercise of power or constrain it [David Cross and Karolewski 2017]. In this paper, we examine how EU foreign policy discourse, and the role conceptions and prescriptions it conveys, can be instrumental in enabling or containing the EU's exercise of power.…”
Section: Contextsmentioning
confidence: 99%
“…The choice of our empirical case -EU role conceptions and prescriptions in relation to the EaP, and to Ukraine in particularis not accidental. Relevant literature argues that the problematic future of the EaP (with visa-free entry regimes, Association Agreements and Deep and Comprehensive Free Trade Agreements (DCFTA) in place, yet with no promise of EU membership in view) and the Ukraine crisis together pose a challenge to the EU's foreign policy and the EU's exercise of power in this geopolitical region (see the 2017 Special Issue "Europe's Hybrid Foreign Policy: The Ukraine-Russia Crisis" edited by [Davis Cross and Karolewski 2017]). David Cross and Karolewski [2017: 3] specifically argue that the Russia-Ukraine crisis serves as a "critical juncture and catalyst for shaping the EU's power" -"constraining or enabling the EU's exercise of power".…”
Section: Introductionmentioning
confidence: 99%